Systemy zarządzania kosztami sprzyjające procesowi wytworzenia produktów - Pewniak-Kaliska, Olga (Manufacturing-Friendly Cost Management Systems, 2006)
The main purpose of the paper is to present manufacturing-friendly cost management systems. The paper depicts target costing and kaizen costing, two of the most popular systems, regarding their relative merits in strategic cost management and operational improvement and control.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 329-339